SharePoint Designer 2013 - Jesperson, Ryan, Dr.; Safari eBooks ([Place of publication not identified] : Intellezy, 2017)
"This course is designed for advanced Microsoft SharePoint site owners and administrators who want to integrate data sources, customize content types, and automate common tasks using workflows. Students will learn about SharePoint Designer and connecting to sites, explore the interface and learn about Designer best practices. Additionally, students will create and modify libraries and lists using Designer, and modify site settings using Designer. Students will get an introduction to workflows and create list and site workflows, adding stages and steps, work with workflow settings, create variables, error check, and publish workflows. Students will learn about important workflow actions, then view a complete list workflow demonstration."--Resource description page.
Title from resource description page (Safari, viewed July 6, 2017).
Presenter, Ryan Jesperson.
Keywords: Microsoft SharePoint (Electronic resource); Streaming video; Business; Information technology; Teams in the workplace; Information resources management; Electronic books